2003
DOI: 10.1097/00003677-200301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Vascular Remodeling

Abstract: Exercise produces a powerful angiogenic stimulus within the active muscle that leads to a functionally important increase in capillarity. Further, exercise can increase flow capacity by enlarging the caliber of arterial supply vessels. These adaptations are achieved by the processes of angiogenesis and arteriogenesis, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
16

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 9 publications
5
132
0
16
Order By: Relevance
“…Several studies have implicated VEGF in skeletal muscle angiogenesis regulation induce by acute aerobic or resistance exercise in both human and animals. [5][6][7][8][9][10][11] Furthermore, it has been shown that training also induce modifications of VEGF mRNA and protein expression. [12][13][14][15][16] Chronic pathological conditions, such as Chronic Obstruction Pulmonary Disease (COPD) and diabetes, 17,18 induce capillary rarefaction suggesting that VEGF is also important in the maintenance of adult skeletal muscle microvasculature.…”
Section: Angiogenesis Muscle Plasticity and Muscle Homeostasismentioning
confidence: 99%
“…Several studies have implicated VEGF in skeletal muscle angiogenesis regulation induce by acute aerobic or resistance exercise in both human and animals. [5][6][7][8][9][10][11] Furthermore, it has been shown that training also induce modifications of VEGF mRNA and protein expression. [12][13][14][15][16] Chronic pathological conditions, such as Chronic Obstruction Pulmonary Disease (COPD) and diabetes, 17,18 induce capillary rarefaction suggesting that VEGF is also important in the maintenance of adult skeletal muscle microvasculature.…”
Section: Angiogenesis Muscle Plasticity and Muscle Homeostasismentioning
confidence: 99%
“…Arterial adaptations associated with exercise may be induced through a direct shear-stress mechanism related to increased blood flow, [44][45][46] or indirectly through reductions in cardiovascular disease risk factors, for example, blood lipids, circulating factors such as oxidants, blood pressure, blood glucose, and body fat. Although we did not measure cardiovascular disease risk factors, a recent study found that FMD improves after short-term exercise (8 weeks) without moderation of said factors.…”
Section: Nmes-induced Arterial Health Improvementsmentioning
confidence: 99%
“…Athletic conditioning induces angiogenesis that enhances tissue perfusion and oxygenation, mitigates flow resistance, reduces blood pressure, and enhances ejection fraction, which slows heart rate via the Starling mechanism [24, 270,[302][303][304][305][306][307][308][309][310][311][312][313][314][315][316][317]. Allostatic load accelerates capillary senescence [318][319][320] that increases vascular resistance, impairs tissue and organ perfusion, inhibits glucose uptake, and causes diabetes and essential hypertension [142,192,231,232,267,273,276,277,279,[321][322][323][324][325][326][327].…”
Section: The Capillary Gate Mechanismmentioning
confidence: 99%